The Multiple Regulatory Relationship Between RNA-Chaperone Hfq and the Second Messenger c-di-GMP - Fu, Yang; Yu, Zhaoqing; Zhu, Li; Li, Zhou; Yin, Wen; Shang, Xiaodong; Chou, Shan-Ho; Tan, Qi; He, Jin (Frontiers in Microbiology, 2021)
RNA chaperone protein Hfq is an important post-transcriptional regulator in bacteria, while c-di-GMP is a second messenger signaling molecule widely distributed in bacteria. Both factors have been found to play key roles in post-transcriptional regulation and signal transduction pathways, respectively. Intriguingly, the two factors show some common aspects in the regulation of certain physiological functions such as bacterial motility, biofilm formation, pathogenicity and so on. Therefore, there may be regulatory relationship between Hfq and c-di-GMP. For example, Hfq can directly regulate the activity of c-di-GMP metabolic enzyme or alter the c-di-GMP level through other systems, while c-di-GMP can indirectly enhance or inhibit the hfq gene expression through intermediate factors. In this article, after briefly introducing the Hfq and c-di-GMP regulatory systems, we will focus on the various direct and indirect regulation reported between Hfq and c-di-GMP, aiming to compare and link the two regulatory systems to further study the complicated physiological and metabolic systems of bacteria, and to lay a solid foundation for drawing a more complete global regulatory network.